"It's Not Like Chasing Chanel:" Spending Time, Investing in the Self, and Pandemic Epiphanies. Issue 2 (May 2023) - Ravenelle, Alexandrea J.; Kowalski, Ken Cai
The Covid-19 pandemic has greatly impacted the labor market and given rise to the Great Resignation. Drawing on a mixed methods panel study of 199 precarious and gig-based workers, we analyze how a changing conception of free time during the Covid-19 pandemic led low-wage service workers to seek more fulfilling careers. Whereas most workers initially perceived free time in terms of opportunity costs, they later reconceived this time as enabling an investment in personal growth, moving from "spending time" making money to "investing time" in themselves. This shift in temporal experience is expressed through the adoption of a "work passion" logic and "pandemic epiphanies" that motivated respondents to seek self-affirming and potentially more lucrative work opportunities.